Penerapan Kebijakan Artificial Intelligence, Digitalisasi dan Rasionalisasi Industri Asuransi oleh Otoritas Jasa Keuangan RI - Karso, A. Junaedi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
To support the digitization of Artificial Intelligence in the life insurance industry, OJK Regulation Number 13/POJK.02/2018 was issued concerning Digital Financial Innovation in the Financial Services Sector. This regulation contains provisions that oversee the supervision and regulation of the digital financial industry that transforms in business processes and the provision of services to consumers by optimizing the use of digital tools,